Disseminated cutaneous larva migrans in a 7-year-old patient - Lopes, Vitor Valente (2018)
Introduction: Cutaneous larva migrans is a cutaneous infestation caused by zoonotic nematode larvae commonly due to hookworms such as the Ancylostoma braziliense. Case report: Herein we report a case of a 7-year-old child to the Emergency Department complaining of erythematous papular itching lesions on his right elbow, wrist and knee. He had no previous history of contact with sand or animals. The lesions in his right elbow presented impetiginization. Ivermectin 200mcg/kg/day treatment was initiated and oxacillin associated. On the third day of treatment, the patient was discharged with complete resolution of the lesions. Coclusion: The reported case assumes importance because it is a common and benign disease, but due to an unusual presentation was not diagnosed early. The disseminated form commonly may require hospitalization and prolonged treatment as presented